Putting yourself into others' shoes : role-play benefits preschoolers' social understanding - Shen, Pinxiu (2013)
Theory of Mind (ToM) is the ability to ascribe mental states such as beliefs, desires, and intentions to oneself and others (Premack & Woodruff, 1978). It is closely related to preschoolers’ behavioral control (e.g., Carlson, Moses, & Breton, 2002; Frye, Zelazo, & Palfai, 1995), academic competence (Blair and Razza, 2007), and social competence (Tan-Niam, Wood, & O’Malley, 2000). Past research has shown that Singaporean preschoolers had a slower ToM development as compared to Chinese, Korean, and North American children (Qu et. al, 2009; Qu et al., 2010, Shen & Qu, 2010). A training program to improve false belief understanding amongst Singaporean preschoolers is thus necessary. Although role-play has been positively associated with ToM development (e.g., Jenkins & Astington, 2000), none of the previous ToM training studies have employed role-play as a training methodology. This study examined the effectiveness of a role-play intervention program in improving preschoolers’ ToM ability. [2nd Award]